2022
DOI: 10.3390/pr10050988
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Volatile Compounds during Grape Brandy Production from ‘Cabernet Sauvignon’ and ‘Syrah’ Grape Varieties

Abstract: Grape-based brandies are one of the most popular alcoholic beverages in the world. The most popular one, Cognac, comes from the Charentes region of Southwest France, and it is mostly produced from the grape variety ‘Ugni Blanc’. However, wines destined for the elaboration of wine spirits also come from different white grape varieties; ‘Colombard’, ‘Folle Blanche’, ‘Montils’, and ‘Semillon’. In this study, the possibility of using the red grape varieties ‘Cabernet Sauvignon’ and ‘Syrah’ was investigated with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…However, diethyl succinate and 2-phenylethyl acetate were significant odor-active chemicals in this distillate, and these esters contributed to the sweet rose fragrance of the spirit [73]. Lončarić et al [82] found in wine spirits that isopropyl tetradecaonate, ethyl hexadecaonate, ethyl cis-9-octadecanoate, and phenethyl acetate were esters responsible for the primary aroma derived from grapes, while ethyl hexanoate and ethyl octanoate were more likely to be developed during the fermentation process. Januszek et al [83] found nearly 60 esters in apple spirits, with methyl and ethyl esters forming the largest group, to which 26 different compounds were assigned.…”
Section: Ethyl Hexadecanoatementioning
confidence: 90%
“…However, diethyl succinate and 2-phenylethyl acetate were significant odor-active chemicals in this distillate, and these esters contributed to the sweet rose fragrance of the spirit [73]. Lončarić et al [82] found in wine spirits that isopropyl tetradecaonate, ethyl hexadecaonate, ethyl cis-9-octadecanoate, and phenethyl acetate were esters responsible for the primary aroma derived from grapes, while ethyl hexanoate and ethyl octanoate were more likely to be developed during the fermentation process. Januszek et al [83] found nearly 60 esters in apple spirits, with methyl and ethyl esters forming the largest group, to which 26 different compounds were assigned.…”
Section: Ethyl Hexadecanoatementioning
confidence: 90%
“…Norisoprenoids and terpenes produced by the metabolism of isoprene mostly generated a pleasant fragrance. Although the content of isoprene-derived volatiles was low in grape fruits, their low sense threshold greatly contributed to grape aroma [43,44], which was an important component influencing the aroma of grape varieties. Two norisoprenoids and eight terpenes were detected in Cabernet Sauvignon berries (Table 6).…”
Section: Isoprene-derived Volatilesmentioning
confidence: 99%
“…Those compounds give sharp and unpleasant flavour. The tail fraction contains, acetic acids and fusel oils, such as propyl, butyl and amyl alcohols and their isomers, that are associated with unpleasant aroma attributes (Bohn et al, 2022).The maximum alcohol content in the middle (heart) cut of fruit distillates after distillation might be 86% vol, although in practice it is usually around 65-75% vol, depending on the distillation apparatus used (Durr, 2010;Lukić et al, 2011;Esteban-Decloux, et al, 2021;Tian-Tian et al, 2022;Lončarić et al, 2022). After distillation is completed, the fresh highproof distillate has to storage for a period of time to harmonize.…”
Section: Introductionmentioning
confidence: 99%